Tafsir Aḥkām dan Legitimasi Kekuasaan Abbasiyyah: Studi atas Tafsir an-Nukat wa al-‘Uyūn dan Pemikiran Politik al-Māwardī - Saldiman, Muhammad Ramli; Nurdin; Zafa Junarif (Jurnal Diskursus Islam, 2026)
This article examines the interpretation of aḥkām as a field of struggle between revelation, law, and power in classical Islamic tradition. The study focuses on the thoughts of Imam al-Māwardī (d. 450 AH/1058 AD), a qāḍī al-quḍāt who lived during the Abbasid political legitimacy crisis when the caliph's authority was eroded by the military domination of the Buwayhid dynasty. Through an interdisciplinary analysis of the exegetical work an-Nukat wa al-'Uyūn and the political treatise al-Aḥkām al-Sulṭāniyyah, this study demonstrates that al-Māwardī's exegesis was not merely an academic activity, but rather an intellectual strategy to maintain social stability and the continuity of the caliphate symbol. By comparing al-Māwardī's views with those of other exegetes such as al-Ṭūsī (Shi'a), al-Qusyairī (Maliki), an-Nasafī (Hanafi), and Ibn Taimiyyah (Hambali), this article reveals how the concepts of obedience (ṭā'ah) is constructed differently according to their respective theological-political contexts. Research findings confirm that the interpretation of aḥkām is a historical product that is never neutral from political interests, but at the same time offers an ethical-normative framework for governance. Theoretically, this study reinforces the argument that the interpretation of sacred texts always takes place within a specific social space and is colored by the power relations that surround it.